Electrochemical Impedance Spectroscopy and its Applications - Lasia, Andrzej (Springer, 2014)
My first practical contact with electrochemical impedance spectroscopy (EIS) was during my postdoctoral training in the laboratory of Prof. Ron W. Fawcett at the University of Guelph, Ontario, Canada, in 1975. At that time I was using ac voltammetry on a dropping mercury electrode. Since then, the technique and equipment have evolved significantly. I was continually using EIS in subsequent years in the kinetics of the reduction of metal cations in nonaqueous solvents to determine the kinetics of hydrogen evolution, adsorption and absorption into metals, impedance of porous electrodes, and electrocatalytic reactions. After a series of seminars on the impedance spectroscopy in the laboratory of Prof. Brian Conway in Ottawa in 1994, he encouraged me to write a review in Modern Aspects of Electrochemistry, which was published in 1999. Prof. Conway has also asked me to write a second chapter in Modern Aspects on the impedance of hydrogen adsorption, absorption, and evolution (2002). Later, Prof. M. Schlesinger asked me to write yet another chapter on the impedance of porous electrodes (2009). This book originated from my previous reviews and lectures at various universities. The purpose of this book is to present the concept of impedance, impedance of electrical and electrochemical systems, its limitations, and certain applications. The available books on EIS were written either by physicists or engineers, and I wanted to present it from the chemist’s point of view. Some knowledge of electrochemistry is necessary to understand the developments of kinetic equations. I hope that it will be useful to students who are just starting to use this technique and to others already using it in their research. The book contains theory and applications, numerical examples shown in the text, and exercises with full solutions on the Internet. First, electrical circuits containing resistances only are presented, followed by circuits containing R, C, and L elements in transient and ac conditions. To understand the concept of impedance, the notions of Laplace and Fourier transforms are presented and must be understood thoroughly. In this chapter, impedance plots are also presented, along with several examples for various circuits. Next, methods for determining impedances, including fast Fourier transform-based techniques, are discussed.
Keywords: Impedance spectroscopy; Spectrum analysis; Chemistry; Electrochemistry